Mutations Selectively Evolving Peroxidase Activity Among Alternative Catalytic Functions of Human Glutathione Transferase P1-1 - Aram Ismail; Bengt Mannervik (MDPI AG, 2024)
Glutathione transferases are detoxication enzymes with broad catalytic diversity, and small alterations to the protein's primary structure can have considerable effects on the enzyme's substrate selectivity profile. We demonstrate that two point mutations in glutathione transferase P1-1 suffice to generate 20-fold enhanced non-selenium-dependent peroxidase activity indicating a facile evolutionary trajectory. Designed mutant libraries of the enzyme were screened for catalytic activities with alternative substrates representing four divergent chemistries. The chemical reactions comprised aromatic substitution, Michael addition, thiocarbamoylation, and hydroperoxide reduction. Two mutants, R1 (Y109H) and an R1-based mutant V2 (Q40M-E41Q-A46S-Y109H-V200L), were discovered with 16.3- and 30-foldincreased peroxidase activity with cumene hydroperoxide (CuOOH) compared to the wildtype enzyme, respectively. The basis of the improved peroxidase activity of the mutant V2 was elucidated by constructing double-point mutants. The mutants V501 (Q40M-Y109H) and V503 (E41Q-Y109H) were found to have 20- and 21-fold improvements in peroxidase activity relative to the wildtype enzyme, respectively. The steady-state kinetic profiles of mutants R1 and V2 in the reduction of CuOOH were compared to the wildtype parameters. The kcat values for R1 and V2 were 34- and 57-fold higher, respectively, than that of the wildtype enzyme, whereas the mutant Km values were increased approximately 3-fold. A 10-fold increased catalytic efficiency (kcat/Km) in CuOOH reduction is accomplished by the Tyr109His point mutation in R1. The 23-fold increase of the efficiency obtained in V2 was caused by adding further mutations primarily enhancing kcat. In all mutants with elevated peroxidase activity, His109 played a pivotal role.